Dealing with Mental Health in Online Learning: A Retrospect on ELT Teachers and EFL Learners during COVID-19 Pandemic - Ferdous , Asma-Ul-; Shifat, Nazia Forhin (REiLA : Journal of Research and Innovation in Language, 2020)
This paper intends to depict the mental health of English Language Teaching (ELT) teachers and English as Foreign Language (EFL) learners at a tertiary level during the COVID-19 pandemic. The educational boards across the globe have been forced to transition to smart classrooms, digital platforms, and effective teacher training programs in online delivery methods. In Bangladesh, the networking system and the management system are being run with care to ensure online classes at tertiary levels. This study showed how ELT teachers and EFL learners experience diverse and innumerable inconveniences due to geographical locations, finance and other systematic online education problems during the pandemic. The study found results which showed what makes them susceptible to anxiety, frustration, depression, which injure their mental health. Getting habituated to new study techniques, cooperating with the lack of laboratories and other required study materials, network connectivity problems, and the harshness of COVID-19 make their living challenging and unneeded mental stress. Quantitative data has been collected through Google questionnaire, and qualitative data has been collected through semi-structured interviews over telephone and online messaging. The results showed that despite continually searching for a way to overcome various troubles, teachers and students get drown into worsening mental health.